Connectivity and dispersal patterns of protected biogenic reefs:Implications for the conservation of modiolus modiolus (L.) in the irish sea - Gormley, Kate; Mackenzie, Clara; Robins, Peter; Coscia, Ilaria; Cassidy, Andrew; James, Jenny; Hull, Angela; Piertney, Stuart; Sanderson, William; Porter, Joanne (PLOS ONE, 2015)
Biogenic reefs created by Modiolus modiolus (Linnaeus, 1758) (horse mussel reefs) are marine habitats which support high levels of species biodiversity and provide valuable ecosystem services. Currently, M. modiolus reefs are listed as a threatened and/or declining species and habitat in all OSPAR regions and thus are highlighted as a conservation priority under the EU Marine Strategy Framework Directive (MSFD). Determining patterns of larval dispersal and genetic connectivity of remaining horse mussel populations can inform management efforts and is a critical component of effective marine spatial planning (MSP). Larval dispersal patterns and genetic structure were determined for several M. modiolus bed populations in the Irish Sea including those in Wales (North Pen Ll͵n), Isle of Man (Point of Ayre) and Northern Ireland (Ards Peninsula and Strangford Lough). Simulations of larval dispersal suggested extant connectivity between populations within the Irish Sea. Results from the genetic analysis carried out using newly developed microsatellite DNA markers were consistent with those of the biophysical model. Results indicated moderately significant differentiation between the Northern Ireland populations and those in the Isle of Man and Wales. Simulations of larval dispersal over a 30 day pelagic larval duration (PLD) suggest that connectivity over a spatial scale of 150km is possible between some source and sink populations. However, it appears unlikely that larvae from Northern Ireland will connect directly with sites on the Ll͵n or Isle of Man. It also appears unlikely that larvae from the Ll͵n connect directly to any of the other sites. Taken together the data establishes a baseline for underpinning management and conservation of these important and threatened marine habitats in the southern part of the known range.